Modal Sosial: Apakah Penting Dalam Penyelesaian Pinjaman di Lembaga Keuangan Mikro Syariah? - saida, umi; Abadi, M. Kurnia Rahman; Prasetiyo, Luhur (ITB AAS INDONESIA Surakarta, 2024)
This study examines the significance of social capital in Islamic microfinance at BMT La Tansa Gontor. The research uses a systematic review of theoretical and empirical literature. The findings show that group loans with joint liability are effective in overcoming credit market challenges for the impoverished. Peer selection, monitoring, and pressure play a role in this effectiveness. However, the empirical literature suggests that social capital is a complex concept with varying effects on performance. Factors like trust, cultural homogeneity, and peer pressure have a greater influence on repayment compared to family groups. The implications of this research are practical and social. It highlights the need to consider social capital in different areas before implementing microfinance programs. It also emphasizes the importance of forming groups with trustworthy individuals and helping those affected by external factors. Lastly, it suggests avoiding family groups. The originality of this research lies in its comprehensive analysis of social capital and its impact on group performance.